ANSYS research of shape memory effects in cross-linked polyethylene products - Smetannikov, Oleg Yur’yevich; Faskhutdinova, Yuliya Borisovna; Subbotin, Evgeniy Vladimirovich (Computational Continuum Mechanics, 2020)
This work focuses on determining the causes of axial shrinkage of heat-shrinkable pipes made of cross-linked polyethylene at the expansion stage of their production process and the ways to eliminate this problem. For this purpose, thermomechanical behavior of products made of polymer materials with shape memory was numerically simulated. First, an appropriate physical model was selected in the ANSYS package to describe the thermomechanical behavior of polymer materials with shape memory, an experimental program was developed and implemented to identify the material constants of cross-linked polyethylene, and several verification tests were performed. Then, a simplified numerical simulation of the thermomechanical behavior of the heat-shrinkable tube was performed using the ANSYS software package, which does not take into account the movement of the work piece through the expander cavity. To eliminate longitudinal shrinkage, it is proposed to preserve the longitudinal size of the work piece by applying an axial force of a certain value. The axial force values corresponding to a longitudinal shrinkage not exceeding 1% and a 15% longitudinal shrinkage were found. It was established that the longitudinal shrinkage is caused by the extremely high axial force. The last section of the article presents a numerical simulation of the real technological stage of expansion of a heat-shrinkable tube. The values of the axial force acting in the work piece are calculated when the feed and extraction speeds of the work piece from the expander are equal to ensure the constancy of its length in the first case and when the initial elongation reaches 15% in the second case. The calculated data confirm the initial assumption about the causes of longitudinal shrinkage.
Keywords: shape memory; cross-linked polyethylene; shrinkable tube; thermomechanical behavior